Optimalisasi Wisata Alam Danau Toba dalam Pengembangan Bahan Ajar Bahasa Indonesia bagi Penutur Asing (BIPA) - Dhevrida Yusuf Bagus Setiyawan; Dinda Yusnita Mirillia Rahma; Muhammad Ridhwan Izzudin; Sagita Adekeysa Hamy Danira; Kundharu Saddhono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study uses a qualitative descriptive method to explore the potential of Lake Toba as an open-ended material in learning Indonesian for Foreign Speakers (BIPA). The research findings show that the geographical uniqueness of Lake Toba as a tourist destination offers opportunities for enriching relevant vocabulary for BIPA learners. In addition, the cultural elements typical of Lake Toba, such as traditions, arts, and customs, are rich learning resources in supporting language and culture teaching simultaneously. To maximize this potential, teaching materials are developed through interactive modules, learning videos, and virtual tours that present an immersive learning experience. This approach not only improves learners' language skills but also creates a deep emotional connection with the material, because learners can experience the beauty of Indonesian culture directly through the media provided.